Legal Aspects of The Elimination of Agricultural Land use in Regional Spatial Planning - Irene Vera Purba; I Gusti Ayu Ketut Rachmi Handayani; Lego Karjoko (Universitas Muhammadiyah Surakarta, 2025)
Spatial planning is crucial in regulating land use and utilization for sustainable development. However, in practice, there are still discrepancies between spatial planning and development implementation in various regions, which result in regional development imbalances, environmental degradation, and resource constraints. This research analyzes the factors causing the mismatch between spatial planning and actual development, particularly in the context of the removal of agricultural land use in the spatial planning of Surakarta City, and examines the impact of these issues. The method used in this research is normative legal research with a conceptual approach and analysis of the applicable laws and regulations. The research results indicate that inconsistencies in satial planning occur due to overlapping policies, inconsistent planning revisions, and weak supervision in implementing regulations. The conversion of agricultural land into non-agricultural areas threatens food security and negatively impacts ecosystem balance and environmental carrying capacity. Therefore, synergy between the government, society, and the private sector is needed in formulating and implementing spatial planning based on sustainability principles. Strengthening regulations, providing incentives for the preservation of agricultural land, and utilizing digital mapping technology can address this issue to achieve development that is in harmony with environmental carrying capacity.